Color stability of an artificially aged nanofilled composite resin post-cured with different techniques - Souza, Lais Sampaio (J Dent Res Dent Clin Dent Prospects, 2021)
Background. Post-cured composite resins exhibit improvements in physical and mechanical properties due to additional polymerization conversion. However, the post-curing techniques might influence the color stability of composite resin materials. Thus, this study evaluated the color stability of a nanofilled composite resin (Filtek Z350 XT - 3M ESPE) subjected to different post-curing techniques. Methods. Sixty samples (color A2) were randomly allocated to six experimental groups (n=10): G1: photoactivation (P) (control); G2: P + microwave oven with distilled water; G3: P + microwave oven without distilled water; G4: P + conventional oven; G5: P + dry-heat sterilizer; G6: P + steam autoclave. All the groups were stored in distilled water for 60 days and immersed daily in 5 mL of a coffee solution for 3 minutes. The color readings (CIEL*a*b* system) were performed at two different time intervals, initially and after 60 days, in a reflectance spectrophotometer (UV-2600; Shimadzu). The colorimetric readings were performed using the Color Analysis software (CIEL*a*b* system). Results. Group G6 exhibited significantly low values of total color change (ΔE=13.16). The control (ΔE=15.32) and G5 (ΔE=15.49) groups exhibited intermediate values, with no difference between them. In turn, the groups in which the resin was heated in a microwave (G2 ΔE=18.55 and G3 ΔE=19.45) exhibited the most significant color changes (one-way ANOVA and Tukey test, P ≤0.05). Conclusion. Steam autoclave post-polymerization increased the color stability of the nanofilled resin subjected to artificial aging and coffee immersion.